P8 Adolescent psychosocial history using headss in a tertiary paediatric emergency department. (18th November 2019) - Sullivan, K; Samarendra, H; Malbon, K; Orteu, D
Abstract : Aims: To describe current practices and referral outcomes using HEADSS psychosocial screening for adolescents presenting to the Emergency Department at a tertiary metropolitan referral hospital. Methods: Hospital records of patients aged 13 to 20 attending the emergency department were reviewed over a 4-week period. Basic patient demographics, presenting complaint and the role of the health professional documenting the HEADDSS assessment was noted. Records were assessed for documentation of psychosocial history items in accordance with the HEADSSS psychosocial screening tool. The number and type of referrals resulting from HEADSS screening was recorded. Data was analysed using basic statistical methods. Results: 363 adolescents aged 13 to 20 years attended the Emergency Department during the study period. Documentation of persons present during HEADSS screening was often incomplete However, only 7% of adolescents were seen alone. HEADSS screening was largely completed by doctors, with just 17% of performed by nurses. Overall, HEADSS screening rates were poor. 43% of patients were not asked about any aspect of HEADSS psychosocial screening. 60% of adolescents were asked about at least one category, but less than 2% had a complete HEADSS screening performed. Home, education and substance use were the most frequently asked about categories. Activities, mental health and sexuality were asked about less commonly, while eating and body image were rarely discussed. 118 referrals were made as a result of HEADSS assessments; which constituted 54% of all encounters in which at least 1 category was screened. Referrals were limited in their scope, the majority being made to Social Services and safeguarding; smaller numbers were made to CAMHS, Red Thread and local Sexual Health services. Conclusion: The use of HEADSS psychosocial screening, which was largely performed by doctors, was inadequate amongst the 13 to 20 year age group. The high rate of referral when HEADSS screening was performed suggests it is of value. This data also suggests a need for multidisciplinary education around HEADSS screening, and exploration of referral pathways to other services that address the needs of young people presenting to the Emergency Department.